Malcolm X : by any means necessary : a biography - Myers, Walter Dean, 1937-2014. (New York : Scholastic, 1993)
As a fourteen-year-old, he was Malcolm Little, the president of his class and a top student. At sixteen, he was hustling tips at a Boston nightclub. In Harlem, he was known as Detroit Red, a slick street operator.
Keywords: X, Malcolm, -- 1925-1965 -- Juvenile literature; X, Malcolm, -- 1925-1965.; Black Muslims -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Black Muslims; African Americans -- Biography